The Influence of Influencers, Trustworthiness, and Perceived Quality on Purchase Intention with Brand Attitude as a Moderator - Ayudiah, Irma Sitie Nur; Widyanti, Ratri Nurina (Golden Ratio of Data in Summary, 2025)
This study aims to examine the influence of perceived influencer trustworthiness and perceived quality on the intention to purchase beauty products with attitude toward the brand as a moderation variable. This study uses a quantitative approach with a questionnaire method. The data used is primary data, which is directly obtained from the respondents' answers through questionnaires. The distribution of the questionnaire is carried out through the Google Form platform by sending a link that contains the arrangement of questions and respondents' biodata. The analysis was carried out with the help of the IBM SPSS statistical program version 26. The results of the study show that Perceived Influencer Trustworthiness has a negative and insignificant effect on the Intention to Purchase of beauty products. Perceived Quality has a negative and insignificant effect on the Intention to Purchase of beauty products. Perceived Influencer Trustworthiness and Perceived Quality do not have a stimulant effect on the Intention to Purchase of beauty products. Attitude Toward the Brand is not able to moderate the influence of Perceived Influencers on the Intention to Purchase of beauty products. Attitude Toward the Brand is not able to moderate the influence of Perceived Quality on the Intention to Purchase of beauty products.